Peace in the Post-Reformation. - Bossy, John (Birkbeck Lectures, 1995., 2003)
Christians are supposed to love their neighbours, including their enemies. This is never easy. When feud and honour are common realities, it is even harder. This highly original book sketches the 'moral tradition' of human (not political) peace-making in four western European countries between the Reformation and the eighteenth century.